(untitled) (Global Journal of Human-Social Science, 2019)
The study investigated climate change related factors and management of primary schools in Benue State. Two research questions and two hypotheses guided the study. Descriptive survey research design was adopted for the study. The population comprised 15,987 teachers from 2,407 primary schools in Benue State. A total of 1000 teachers from 122 primary schools were selected using multi-stage sampling strategy (Proportionate stratified random sampling and incidental simple random sampling techniques). Climate Change Related Factors Questionnaire (CCRFQ) was used for data collection. The data collected was analyzed using mean and standard deviation to answer the research questions and chi-square to test the hypotheses at 0.05 level of significance. The findings revealed that changing rainfall patterns and flood significantly impact on the management of primary schools in Benue State.